Managing Risk of Supply Disruptions: Incentives for Capacity Restoration. (18th April 2012) - Hu, Xinxin; Gurnani, Haresh; Wang, Ling
Abstract : A supplier facing the prospect of disruption has to decide whether or not to invest in restoration capability. With restoration capability, if disruption occurs, additional costly effort can be exerted to rebuild capacity, although its outcome is uncertain. We study how a firm (buyer) can use incentive mechanisms to motivate a supplier's investment in capacity restoration, and compare this approach with the traditional approach of diversifying part of the order to an expensive but reliable supplier. Under a Restoration Enhancement (RE) strategy, the buyer uses price and/or order quantity incentives to encourage the supplier's restoration investment decision. Two different cases are considered—when the incentive is committed to ex ante (prior to disruption) and when it is committed to ex post (after disruption). In contrast, under a Supplier Diversification (SD) strategy, the buyer splits orders between a reliable supplier and an unreliable supplier to hedge against the disruption risk. Here, the buyer does not provide any separate incentive to the unreliable supplier. Our analysis indicates that under the RE strategy, where the buyer offers incentives, both the buyer and the supplier (weakly) prefer the ex ante commitment over the ex post one. Furthermore, the RE strategy is preferred over the SD strategy when the unreliable supplier's restoration outcome is more predictable or when a high restoration outcome is more likely. However, the buyer's preference for the SD strategy increases as market demand increases.